Internal efficacy and political trust: Evaluating political institutions through pandemic crisis policy - Koivula, Aki; Kestilä-Kekkonen, Elina (SAGE Publications, 2026)
The COVID-19 pandemic presented a rare opportunity to investigate the factors influencing citizens’ trust in political institutions in a context of crisis. Grounded in the trust-as-evaluation model and the distinction between specific and diffuse political support, we analysed a 3-wave longitudinal dataset (n = 543) from the Finnish population (2019–2021) to assess how satisfaction with the government’s COVID-19 policy influenced political trust and under what conditions. We focused on the moderating role of internal political efficacy. Results showed that trust became more evaluative over time, confirming the temporal link between policy satisfaction and trust. Internal efficacy was found to moderate this effect: individuals with very low or very high efficacy demonstrated minimal shifts in trust, whereas those with moderate or high efficacy exhibited changes in trust tied to their perception of government performance. These findings emphasize the importance of effective policies and political engagement in maintaining trust during prolonged crises.